On the Role of Social Media in the ‘Responsible’ Food Business: Blogger Buzz on Health and Obesity Issues - Lee, Hsin-Hsuan Meg (Journal of business ethics, 2013)
To contribute to the debate on the role of social media in responsible business, this article explores blogger buzz in reaction to food companies’ press releases on health and obesity issues, considering the content and the level of fit between the CSR initiatives and the company. Findings show that companies issued more product-related initiatives than promotion-related ones. Among these, less than half generated a substantial number of responses from bloggers, which could not be identified as a specific group. While new product introductions led to positive buzz, modifications of current products resulted in more negative responses, even if there was a high fit with core business. While promotion-related press releases were received negatively in general, particularly periphery promotion (compared to core promotion) generated most reactions. Our exploratory study suggests that companies can increase the likelihood of a positive reaction if they carefully consider the fit between initiatives and their core business, while taking the notion of ‘controversial fit’, relating to the unhealthy nature of original products, into account. Further research avenues and implications, as well as limitations, are discussed.